2015
DOI: 10.15376/biores.10.2.2130-2142
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Myrcene-based UV-curable Monomer and its Copolymers with Acrylated Epoxidized Soybean Oil: Design, Preparation, and Characterization

Abstract: An innovative myrcene-based ultraviolet curable vinyl ester monomer was synthesized, and its molecular structure was analyzed with Fourier transform infrared spectroscopy and nuclear magnetic resonance ( 1 HNMR and 13 CNMR) analysis. A series of copolymers were also prepared by mixing the myrcene-derived monomer with another vinyl ester monomer, acrylated epoxidized soybean oil, under ultraviolet light. The curing process was monitored using Fourier transform infrared spectroscopy. Ultraviolet curing analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…AESO can be polymerized by UV/VIS light using appropriate photoinitiators and can form a cross-linked polymer network. AESO is already photopolymerized with polycaprolactone diacrylate and polyethylenglycol diacrylate [25], tetrahydrophurphuryl acrylate [26,27], myrcene [28], and various thiols [29,30]. The addition of comonomers improved the mechanical and thermal properties as well as solvent resistance of the resulted polymers.…”
Section: Introductionmentioning
confidence: 99%
“…AESO can be polymerized by UV/VIS light using appropriate photoinitiators and can form a cross-linked polymer network. AESO is already photopolymerized with polycaprolactone diacrylate and polyethylenglycol diacrylate [25], tetrahydrophurphuryl acrylate [26,27], myrcene [28], and various thiols [29,30]. The addition of comonomers improved the mechanical and thermal properties as well as solvent resistance of the resulted polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] However, due to the flexible long aliphatic chain of soybean oil, as much as 50% or more petroleum-based rigid compounds, such as styrene [8,9], acrylate acid [10] and divinylbenzene [11,12], are necessary to make its mechanical or thermal properties acceptable for end use. Recently, with the rapid progress on bio-based materials, the exploration of bio-based compounds to strengthen the polymers derived from soybean oil so as to ensure a higher bio-based content has been frequently reported [5,[13][14][15][16][17]. For instance, acrylated sucrose monomers and tetrahydrofurfural acrylate were co-photopolymerized with AESO to obtain a highperformance coating with a higher bio-based content in Chen's work [13].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [14] synthesized hyperbranched methacrylates (TAHAs) from tannic acid to improve the properties of AESO-based coatings. Yang et al reported the bio-based films with good coating properties derived from AESO and myrcene derivatives [15]. However, it is easy to notice that the volatile organic compounds (VOC) emission during the synthesis process is inevitable and eager to be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…These commercially available or synthesized resins and their composites are attractive for respective merits and have been widely used in coating, adhesive, automobile parts, turbine blade, etc. [7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%